The Mainz internet database of Names on Terra Sigillata (samian ware), Portugal and Spain and the collaborative samian research network - Dannell, Geoffrey B. (2021)
The digital research resource 'Samian Research' offers access to a quarter of a million recorded Samian (Terra Sigillata) stamps found within the Roman Empire and its barbarian borderlands. It comprises the main corpora 'Names on Terra Sigillata', 'Corpus Vasorum Arretinorum' and 'Gestempelte Südgallische Reliefsigillata' and thousands of new finds from various sites added after the printed publication of these books. The resource also offers tools for data exploration, generating dating curves for find-sites, weighted distribution maps and statistical tools to analyse the internal structures of Samian potteries.